Pengaruh Investment Opportunity Set, Ukuran Perusahaan Dan Intensitas Modal Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Holding Dan Investasi Yang Terdaftar di BEI Periode 2019-2023 - Annisa Putri; Nurmala Nurmala; Anita Kusuma Dewi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The value of a company reflects the estimated total assets and potential income it possesses, as well as shareholder expectations regarding its future performance and growth. Firm value serves as a primary focus in making investment decisions. Understanding firm value is key to investment decision-making, performance assessment, and financial management. This research aims to examine the influence of the investment opportunity set turnover, firm size, and capital intensity on firm value. The research population consists of holding and investment sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The sample selection for this research used purposive sampling. Based on the purposive sampling method, 8 companies met the criteria. The analytical tool used to test the hypotheses was interaction testing with IBM SPSS Statistics 2022 software. The results of this research indicate that the investment opportunity set positively affects firm value, firm size positively affects firm value, and capital intensity negatively affects firm value.